Renewed Big Power Competition and the Future of Nuclear Non-Proliferation - Syeda Saiqa Bukhari; Asia Karim (CISS Insight Journal, 2023)
In recent years, nuclear weapons-based deterrence has returned to the forefront of global politics and there is a growing risk of conflict between the US, Russia, and other nuclear powers. The US-Russia bilateral arms control agreements are stalling. Strategic instability is increasing which can create a domino effect on the nuclear non-proliferation regime. After the entry into force of the NPT in 1970, state parties agreed to work for the complete elimination of nuclear weapons. Instead, all nuclear powers are modernizing their nuclear forces. The non-proliferation regime is becoming increasingly discriminatory, in which big powers are supporting certain states in vertically proliferating while constraining others from even accessing nuclear technology for peaceful purposes. These trends indicate that not only shall nuclear disarmament remain a pipedream but even the non-proliferation regime shall be undermined. This study investigates the role of NPT’s nuclear weapon states in fulfilling their non-proliferation commitments and risk reduction. The study concludes that arms control is no longer treated as a priority by the nuclear weapons states. The NPT nuclear-armed states are vertically proliferating and are only interested in those arms control agreements that do not undermine their national security priorities. There are deep fissures in the non-proliferation regime, in which a majority of NPT’s non-nuclear weapon states have sought to ban nuclear weapons sans support of nuclear powers.